Psychological stress and influence factors in elderly patients with mild coronary heart disease: a longitudinal follow-up study in Shanghai, China - Zhang, Yunwei; Wu, Qiyong; Xie, Qiaotao; Xu, Zhimin; Yang, Xiuhui; Luo, Yashuang; Wan, Lingshan; Yang, Ya; Wang, Yibo; Ding, Hansheng (Frontiers in Psychology, 2024)
Introduction: Effective health management is crucial for elderly patients with coronary heart disease (CHD). This study applied a Psycho-Cardiology model to CHD management, aiming to assess psychological stress among patients with mild CHD and identify potential influencing factors to provide substantiating evidence. Methods: This longitudinal study was based on a 9-year follow-up program of a community population in Shanghai, China. A total of 44,553 elderly people were included, with the average age being 74.9 (±10.35) years, and the proportion of female participants being 56.5%. To evaluate and compare the effect of the disease, individuals were categorized into four groups based on their medical records from the past six months, these being (I) a CHD with other chronic diseases group, (II) a CHD only group, (III) non-CHD patients with one (or more) chronic disease group, and (IV) non-patient group. Demographic characteristics, sleep quality and health status of each participants were collected using the Unified Needs Assessment Form for Elderly Care Questionnaire. A multivariate logistic regression was used for statistic analysis. Results: Demographic characteristics differed significantly between the three chronic disease groups (Groups I, II and III) and the non-patient group. Participants in the CHD group reported poorer sleep quality, worse health status, and a more rapid health decline when compared to those with other chronic diseases. Factors such as age, gender, education level, disease duration, and family support were identified as potential influences on the self-reported subjective sleep quality in patients with mild CHD. While age, education level, living status and family support were potential factors influencing the self-assessed health status in participants without CHD (Groups III and IV). Conclusion: Patients with mild CHD may experience lower subjective sleep quality, health status scores, and a faster health-sleep decline, indicating elevated psychological stress. Higher education levels offer a protective effect against this stress, highlighting the importance of psycho-emotional interventions and educational strategies. Additionally, it is important to prioritize early intervention for newly diagnosed cases to aid in illness acceptance. These findings provide crucial insights for managing patients with mild CHD and inform the efficient allocation of healthcare resources.